Pacemaker implantation after balloon- or self-expandable transcatheter aortic valve replacement in patients with aortic stenosis. (25th November 2020) - Bodin, A; Bisson, A; Herbert, J; Lacour, T; Saint Etienne, C; Pierre, B; Deharo, P; Babuty, D; Clementy, N; Fauchier, L
Abstract: Background: The incidence of conduction abnormalities requiring permanent pacemaker implantation (PPI) after transcatheter aortic valve replacement (TAVR) with different devices available in recent years remains a matter of debate. Methods: Based on the administrative hospital-discharge database, we collected information for all patients treated with TAVR between 2010 and 2019 in France. We compared the incidence of PPI after TAVR according to the type and generation of valve implanted. Results: A total of 49, 201 patients with aortic stenosis treated with transcatheter aortic valve replacement (TAVR) using the balloon-expandable (BE) Edwards SAPIEN valve or the self-expanding (SE) Medtronic CoreValve were found in the database. Patients treated with early BE or SE valves had higher Charlson comorbidity and frailty indexes than those treated with later BE or SE valves, and slightly higher EuroSCORE II. Patients treated with SE valves had higher rates of previous pacemaker or defibrillator than those treated with BE valves. Mean (SD) follow-up was 1.2 (1.5 years) (median [interquartile range] 0.6 [0.1–2.0] years). PPI after the procedure was reported in 13, 289 patients, among whom 11, 010 (22.4%) had implantation during the first 30 days (figure 1). In multivariable analysis, using early BE TAVR as reference, adjusted OR (95% CI) for PPI during the first 30 days was 0.88 (0.81–0.95) for latest BE TAVR, 1.40 (1.27–1.55) for early SE TAVR and 1.17 (1.07–1.27) for latest SE TAVR. Compared to early BE TAVR, adjusted HR for PPI during the whole follow-up was 1.01 (0.95–1.08) for latest BE TAVR, 1.30 (1.21–1.40) for early SE TAVR and 1.25 (1.18–1.34) for latest SE TAVR. Conclusion: In patients with aortic stenosis treated with TAVR, our systematic analysis at a nationwide level found higher rates of PPI than previously reported. BE technology was independently associated with lower incidence rates of PPI both at the acute and chronic phases than SE technology. However, this was less apparent than previously reported in this large analysis of unselected patients seen in "real life" practice. Recent generations of TAVR were not independently associated with different rates of PPI than early generations during the overall follow-up. Funding Acknowledgement: Type of funding source: None